Dr. Keynes: economic theory in a diagnostic science - Kevin D. Hoover (University of California, Department of Economics, 2005)
In his own view, economic theory was important to Keynes's work as an economists. Aside from the General Theory, most of his economic writings, however policy oriented make explicit reference to theory. Nevertheless, Keynes's theoretical style is so far from what contemporary economics regards as "theory" that some have dismissed Keynes as a theorist altogether or thought of him as a theorist hampered by the lack of modern mathematical tools. In this paper, I argue to the contrary that Keynes's theoretical style is conditioned by a conception of theory as a diagnostic tool. This is a natural development from Marshall, and conceptually very different from modern macroeconomists. It is nonetheless a very attractive conception of the place of theory in economics.
Keywords: 330